A stability-indicating HPLC-UV method for the quantification of anthocyanin in Roselle (Hibiscus Sabdariffa L.) spray-dried extract, oral powder, and lozenges. Issue 3 (March 2022) - Khan, Nasir Hayat; Abdulbaqi, Ibrahim M.; Darwis, Yusrida; Aminu, Nafiu; Chan, Siok-Yee
Abstract: Hibiscus sabdariffa L. (H.S.) plant and its calyces have received much attention from researchers because of their potential medicinal and nutritional values. Calyces are the major source of anthocyanin in this plant. Therefore, a well-developed, efficient, and accurate analytical method is needed to assure proper standardization and control the quality of H.S. plant herbal and nutraceutical products. The objective of this work is to develop a simple, rapid, stability-indicating HPLC-UV method for the quantitative determination of anthocyanin in spray-dried aqueous extract (SDE), oral powder, and compressible lozenges formulations using Delphinidin-3-O-sambubioside (Dp3S) as a marker compound. The chromatographic conditions were optimized using Eclipse plus® C18 column. The mobile phase comprised water acidified with 0.2% formic acid (FA) and acetonitrile (ACN) (90:10, v/v) using a gradient system at a flow rate of 0.8 mL/min. The detection wavelength was 525 nm. The column was maintained at 45 °C, and the injection volume was 15 μL. The developed method was validated according to the international conference of harmonization (ICH) guidelines for linearity, detection and quantitation limits, accuracy, precision, specificity, and robustness. Forced degradation studies under acid, base, oxidation, heat, and U.V light, were performed on the pure compound, extract, and the H.S. developed formulations. Significant degradation of the compound was observed under all tested conditions except U.V. light, where degradation was minimum. There was no interference from impurities, degradation products, or excipients at the retention time of Dp3S 3.2 min indicating the specificity of the method. The developed method was statistically confirmed to be accurate, precise, and reproducible. This simple, rapid, and specific method can be employed efficiently to determine anthocyanin in H.S. plant extract and nutraceutical products. Graphical abstract: Image 1 Abstract : Hibiscus Sabdariffa L. ; Roselle; Anthocyanin; Delphinidin-3-O-sambubioside; Stability indicating HPLC method; Forced degradation studies.